(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2018)
In this work we will briefly reflect on the tension between the positions that support the absolute need to respect the traditions of ethnic minority cultures and those who perceive in those traditions features contrary to the claims of women’s rights. Finally, special mention will be made of a sentence handed down in the province of Salta in which the tension shown above can be observed in a specific factual case and the response of the right to these situations.